Leaf litter copepods from a cloud forest mountain top in Honduras (Copepoda: Cyclopidae, Canthocamptidae) - Fiers, Frank; Jocque, Merlijn (Zootaxa, 2013)
Five different species of Copepoda were extracted from a leaf litter sample collected on the top (at 2000 m a.s.l.) of a cloud forested mountain in El Cusuco National Park, Honduras. Three of them, one Cyclopidae and two Canthocamptidae are new to science, and are described herein. Olmeccyclops hondo sp. nov. is the second representative thus far known of this New World genus. Moraria catracha sp. nov. and Moraria cusuca sp. nov. are the first formally described members of the genus occurring in Central America. The concept of a “Moraria-group” is considered to be an artificial grouping and is limited here to the genera Moraria and Morariopsis only. The distributional range of this group is essentially Holarctic, with the mountainous regions inHonduras, and probably in westNicaragua, as the southernmost limits in theNew World.